Dissolution of Yugoslavia and migration from and to newly formed states - Rajković Iveta, Marijeta (Array, 2012)
The migration period started in the nineties with the dissolution of Yugoslavia and the beginning of the war. People migrated from and to the Socialist Republics and the Socialist Autonomous Provinces that gradually become independent states. Migrations were forced and/or voluntary, independent or mass, and sometimes planned thanks to the political impulse. Migrants represented minority population in the new environment. They tended to return to their country of domicile by replacing their home or flat with the family that was in the same situation but in other/new state. Most of the newly-formed minorities were autochthon. The mass migration of Serbs took place from Croatia to Serbia and to Bosnia and Herzegovina controlled by Bosnian Serb forces (Serbian Republic). The group and planned migrations of Croats took place from Bosnia, Vojvodina and Kosovo – Janjevci to Croatia. To some extent, some Croats also moved from Boka Kotorska (Montenegro) to Croatia. Despite migrants’ aim to live in their ethnical and confessional environment, and in spite of a great support and help of political elite of that period (for e.g. the former president of Croatia, Franjo Tuđman) and after twenty years of coexistence, minority population is still perceived as „Other“ and is different from the domicile population. Differences are cultural with dialectal specificities. Some of these people live in ghettos. These differences are result of different mentality, customs, and tradition they brought with them from the Balkans. Positive discrimination led to the unacceptance of emigrants. In other words, emigrants enjoyed the economic benefits ( e.g. new houses) that Croats from Croatia did not get, although they were also refugees expelled from their homes during wartime and their houses were destroyed. Migrations of the last twenty years on the territory of Croatia, Serbia, Kosovo, Bosnia and Herzegovina and Montenegro will be presented in this brief presentation. The focus will be on several case studies carried out in Boka Kotorska (Montenegro), Ravni Kotari and Bukovica (Dalmatia). Newspaper articles, internet databases, as well as jokes and graffiti about migrants will be used as well.